Petanque: Mental Training and Kinesthetic Perception of Shooting Accuracy (Department of Physical Education, Sport, Health and Recreation, 2020)
This study aims to determine 1) the difference in the effect of mental imagery training with mental autogenic training on shooting accuracy in petanque sports, 2) the effect of kinesthetic perception on shooting accuracy in petanque sports, 3) the interaction between mental training and kinaesthetic perception on shooting accuracy in petanque sports. The research method used is the experimental method. The data was collected using perception tests and shooting accuracy tests, while the instruments used were shooting tests from FIPJP (Fédération Internationale de Pétanque et Jeu Provençal). Data analysis using ANAVA analysis. The results of this study are 1) Mental imagery training has a greater effect than mental autogenic training on shooting accuracy in Petanque sports, 2) There is an effect of kinesthetics perception on shooting accuracy in Petanque sports, 3) There is an interaction between mental training and kinaesthetic perception of accuracy shooting in petanque sport. So the conclusion of this study, to obtain high accuracy of shooting Petanque, athletes who have high kinesthetic perception should be selected, supported by programmed imagery training.